Incidence of epilepsy among patients with cerebral palsy - Pertin Sianturi; Amir Sarifuddin; Bistok Saing (Paediatrica Indonesiana, 2001)
Epilepsy is a chronic condition due to cerebral function disorders. Epilepsy occurs as a common complication of many neurological disorders such as cerebral palsy (CP) that can affect further brain damage especially if they are with prolonged seizure. The incidence of epilepsy among patients with CP varies between 25-35%. The high incidence of epilepsy among patients with CP suggests that this disorder has common or related origins. We carried out the retrospective study to determine incidence of epilepsy among patients with CP registered within July 1988 to June 1998 in YPAC Medan and to determine whether the incidence of epilepsy differed according to type of CP. Data were compiled from medical records, including name, sex, parity, mothers age, prenatal, perinatal, and postnatal history, and EEG results. Data were analyzed using statistical computer program and its significance was evaluated by chi square test at p < 0,05. There were 67 cases with CP, 53 cases spastic CP, 13 cases mixed CP and one case dyskinetic CP. Of the 67 cases CP, 47,8% male, 52,2% female and mean age 50,3 (SD 36,9) months. There were 25 (37,3%) patients CP associated with epilepsy, 72% general seizures, 20% partial seizures, and 8% infantile spasms. The incidence of epilepsy was significant different among patients with CP associated with type of CP and gestasional age, p < 0,05. We concluded that incidence of epilepsy among patients with CP in YPAC Medan was 37,3% and significantly different among patients with CP according to type CP and gestasional age.